Feasibility of sequential adjuvant chemotherapy with a 3-month oxaliplatin-based regimen followed by 3 months of capecitabine in patients with stage III and high-risk stage II colorectal cancer: JSWOG-C2 study - Tsuruta A; Yamashita K; Tanioka H; Tsuji A; Inukai M; Yamakawa T; Yamatsuji T; Yoshimitsu M; Toyota K; Yamano T; Nagasaka T; Okajima M (Dove Medical Press, 2016)
Atsushi Tsuruta,1,* Kazuki Yamashita,2,* Hiroaki Tanioka,3 Akihito Tsuji,4,5 Michio Inukai,6 Toshiki Yamakawa,7 Tomoki Yamatsuji,8 Masanori Yoshimitsu,9 Kazuhiro Toyota,10 Taketoshi Yamano,11 Takeshi Nagasaka,12 Masazumi Okajima13 On behalf of the Japan Southwest Oncology Group (JSWOG) 1Department of Digestive Surgery, Kawasaki Medical School Hospital, 2Department of Surgery, 3Department of Medical Oncology, Okayama Rosai Hospital, Okayama, 4Department of Medical Oncology, Kobe City Medical Center General Hospital, Kobe, 5Department of Clinical Oncology, Faculty of Medicine, Kagawa University Hospital, Kagawa, 6Department of Medicine, Okayama Saiseikai General Hospital, Okayama, 7Department of Surgery, Kagawa Prefectural Central Hospital, Takamatsu, 8Department of General Surgery, Kawasaki Medical School, Okayama, 9Department of Surgery, Hiroshima City Asa Hospital, Hiroshima, 10Department of Surgery, National Hospital Organization Higashihirosima Medical Center, Higashihiroshima, 11Department of Surgery, Kurashiki Medical Center, 12Department of Gastroenterological Surgery, Okayama University Graduate School of Medicine, Dentistry and Pharmaceutical Sciences, Okayama, 13Department of Surgery, Hiroshima City Hospital, Hiroshima, Japan *These authors contributed equally to this work Background: Six months of oxaliplatin-based chemotherapy is the standard adjuvant chemotherapy for completely resected stage III colorectal cancer (CRC). Also, patients with stage II CRC who are considered to be at high risk of disease recurrence often receive the same adjuvant chemotherapy treatment. We prospectively investigated the extent and degree of neuropathy suffered by stage III and high-risk stage II resectable CRC patients who underwent sequential approach involving 3 months of an oxaliplatin-based regimen followed by 3 months of capecitabine. Patients and methods: Patients with completely resected stage III and high-risk stage II CRC aged ≥20 years were eligible. Patients were treated with folinic acid, fluorouracil, and oxaliplatin (FOLFOX) or capecitabine and oxaliplatin (CAPOX) for 3 months followed by capecitabine (2,500 mg/m2 on days 1–14 every 3 weeks) for 3 months. Primary end points were frequency and the grade of oxaliplatin-induced neurotoxicity as evaluated using the physician-based Common Terminology Criteria for Adverse Events version 4.0 (CTCAE) grading and the patient-based scale, self-reported Patient Neurotoxicity Questionnaire. Results: Ninety-one patients were enrolled and 86 patients assessed. Eighty-four percent of patients completed the planned oxaliplatin-based therapy for 3 months, and 63% of patients completed all treatments for the full 6 months. Overall incidences of grade 3 or 4 peripheral sensory or motor neuropathy according to the CTCAE were 3.5% and 1.2%, respectively. Regarding the peripheral sensory neuropathy, the proportion of Patient Neurotoxicity Questionnaire (grade C–E) and CTCAE (grade 2–4) at months 1.5/3/6 were 11.3/22.1/29.4% and 5.3/4.4/11.3%, respectively (Spearman correlation coefficient: 0.47). Conclusion: A sequential approach to adjuvant chemotherapy with 3 months of an oxaliplatin-based regimen followed by 3 months of capecitabine was tolerated by patients and associated with a low incidence of neuropathy. Keywords: oxaliplatin, peripheral neurotoxicity, adjuvant chemotherapy, Patient Neurotoxicity Questionnaire